Is poverty the mother of crime? Empirical evidence of the impact of socioeconomic factors on crime in India - Ashish Bharadwaj (Atlantic Review of Economics, 2014)
Economic analysis of crime and criminal law addresses the question of individual welfare (utility) maximization through optimal allocation of resources and time in accordance to their relative returns. In this paper I first summarize the theoretical and empirical evidence on the nexus between crime and socio economic indicators. After which I test the hypothesis that people who are vulnerable to fall under the poverty line indulge in criminal activities as a consumption smoothing strategy. I also empirically inspect the role economic growth, unemployment, urbanization and quality of legal system play in inducing property related crimes. India is chosen as the case study because it has to carefully channel its funds and resources towards economic growth, poverty alleviation and crime deterrence concomitantly. The results indicate a positive and statistically significant impact of poverty, inequitable income growth and low quality of the legal system on incidence of total property-related crimes. Moreover, the elasticity figures suggest that poverty has the highest impact on robberies. Most convincing result comes from the figures of elasticity of education with crime where a 10% increase in per capita expenditure on education in India leads to a decline between 9.2-11.2% of overall property crime rates.
Keywords: K10; I25; P46; D63; 330; Crime; Poverty; Economic Growth; Criminal Legal System; Education